Low energy photocatalytic glycerol conversion to high valuable products via Bi2O3 polymorphs in the presence of H2O2. (November 2020) - Limpachanangkul, Paphada; Liu, Licheng; Hunsom, Mali; Chalermsinsuwan, Benjapon
Abstract: In this study, two polymorphs of bismuth oxide were synthesized via the solution-based route for the aqueous phase glycerol transformation to high valuable compounds with low energy photocatalysis in the presence of hydrogen peroxide as the electron acceptor. The results showed that the hydrogen peroxide was deficient to produce OH radicals in tetragonal bismuth oxide ( β -Bi2 O3 ) photocatalyst because it decomposed very fast to H 2 O and O 2 and unoxidized glycerol, resulting in a low glycerol conversion at almost 6.6 times comparing with that of monoclinic bismuth oxide ( α -Bi2 O3 ) photocatalyst. Also, more valuable products could be produced with α -Bi2 O3 photocatalyst system. In addition, the possible mechanisms of hydrogen peroxide on the low energy photocatalytic performances of both bismuth oxide polymorphs were discussed.